Hyperhomocysteinemia Increases Risk of Metabolic Syndrome and Cardiovascular Death in an Elderly Chinese Community Population of a 7-Year Follow-Up Study - Liu, Chang; Liu, Liping; Wang, Yinglu; Chen, Xiaoli; Liu, Jie; Peng, Sheng; Pi, Jingjiang; Zhang, Qi; Tomlinson, Brain; Chan, Paul; Zhang, Lin; Fan, Huimin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Hyperhomocysteinemia (HHcy) and abdominal obesity are risk factors for metabolic syndrome (MetS) and death from cardiovascular disease (CVD). Recent studies have shown a correlation between HHcy and abdominal obesity, suggesting that they may have a combined effect on the risk of MetS and CVD mortality. However, this suspicion remains to be confirmed, particularly in the elderly population. We explored their combined effects on the risk of MetS and CVD mortality among the community population aged 65 and above in China. Methods and Results: This prospective study enrolled 3675 Chinese community residents aged 65 and above in May 2013 with 7-year follow-up of all-cause and CVD mortality. HHcy was defined as the blood homocysteine (Hcy) level >15µmol/L and abdominal obesity as waist circumference (WC) ≥ 90 cm for men and ≥ 80 cm for women (HWC). All participants were grouped into four categories by WC and the blood level of Hcy: NWC (normal WC) /HHcy(−), NWC/HHcy(+), HWC/HHcy(−), and HWC/HHcy(+) . The relationship of combined HHcy and abdominal obesity with MetS and metabolic profile was evaluated by logistic regression analysis and the association of combined HHcy and abdominal obesity with CVD and all-cause mortality evaluated by Cox regression analysis. The prevalence of HHcy, abdominal obesity and MetS in elderly Chinese community residents was 40.1%, 59.3% and 41.4% respectively. Using group without HHcy and abdominal obesity [NWC/HHcy(−)] as reference, the participants of other three groups had significantly higher risk of MetS and its component abnormalities, with HWC/HHcy(+) group having the highest risk (OR=13.52; 95% CI=8.61-14.55). After a median of 6.94 (±1.48) years follow-up, 454 deaths occurred with 135 CVD deaths. Compared with NWC/HHcy(-) group, the risk of 7-year follow-up CVD mortality (HR=1.75; 95% CI=1.02-3.03) and all-cause mortality (HR=1.23; 95% CI=1.04-2.18) of HWC/HHcy(+) group increased considerably after adjustment for major MetS and CVD risk factors. Conclusions: There was high prevalence of HHcy, abdominal obesity and MetS in the elderly Chinese community population. HHcy increased risk of MetS, CVD and all-cause mortality, especially in the populations with abdominal obesity.